Analisis SWOT Sebagai Strategi Meningkatkan Daya Saing Pada Apotek 325 Surabaya - Rachmawati, Anisa; Susanti, Ety Dwi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This research was conducted at Apotek 325 which is located on Jl. Demak No. 325, Dupak, Krembangan District, Surabaya City, East Java. The pharmacy has been established since 2000 where a new business strategy is needed to face increasing competitive and increasing complex business competition. The research method used is a descriptive quantitative approach, using the SWOT method and data collection techniques with primary data and secondary data, in which the author's secondary data is through in-depth interviews, documentation and participatory observations relating to the SWOT analysis owned by Apotek 325 Surabaya. After getting the data then the data will be analyzed with SWOT. The results of the research from the SWOT analysis obtained IFAS results with a total score of 2.01 while for EFAS results with a total score of 2.49. From the results of the SWOT diagram, Pharmacy 325 is in quadrant II, namely the Diversification Strategy. The results of the SWOT Matrix Strategy obtained that the SO Strategy was 1.7, the ST Strategy was 2.91, the WO Strategy was 1.59, and the WT Strategy was 2.8.